Introduction toteaching physical education : principles and strategies. - Shimon, Jane M., ....- (Champaign : Human Kinetics, 2011)
Introduction to Teaching Physical Education: Principles and Strategies is the perfect initiation for undergrads planning to become teachers. The text provides them with a solid background on the physical education field along with the ins and outs they need to know to become successful K-12 professionals. No other introductory text so successfully blends the theoretical, practical, and inspirational aspects of teaching physical education, combining authoritative information with a highly engaging style. This practical, student-friendly text helps students build a strong base of instructional skills as they learn to apply the principles of teaching physical education. In addition to focusing on teaching skills, they will explore the history of physical education, including the two main systems that served as the profession's foundation, and they will learn the purpose of physical education and the standards that are in place to achieve that purpose. They also will examine teaching scope
And sequence, teaching and nonteaching duties and issues, motivational theories and strategies, and principles of behavior management and safeguards. Additionally, students delve into lesson planning, assessment options, technology and online resources, and careers in the field. Introduction to Teaching Physical Education will open students' eyes to the practicalities and realities of the profession. And it comes with several features that will make your job easier: * Sidebars that explicate main concepts to enhance student understanding * An online study resource offering case studies, worksheets that heighten understanding of content and focus on specific skill elements, and blank lesson plan templates * An instructor guide that supplies chapter overviews, discussion questions, lesson ideas, extended learning activities, test and quiz bank questions, and chapter-by-chapter PowerPoint outlines This hands-on resource offers students a wealth of real-world exercises to enhance their
Learning experience and prepare them to enter the teaching profession. It enables students to gain the knowledge and skills they need as they pursue their entry into the teaching profession, and it provides them with the ideal springboard to advance in their coursework.
Keywords: Lichamelijke opvoeding -- Opleiding